Salvage lymphadenectomy in recurrent ovarian cancer patients: Analysis of clinical outcome and BRCA1/2 gene mutational status. Issue 7 (July 2020) - Gallotta, V; Bruno, M; Conte, C; Giudice, MT; Davià, F; Moro, F; Zannoni, GF; Fagotti, A; De Bonis, M; Capoluongo, E; Scambia, G; Ferrandina, G
Abstract: Objective: This study is aimed to analyze the clinical outcome of recurrent ovarian cancer patients bearing isolated lymph-node recurrence (ILNR) who underwent salvage lymphadenectomy (SL). The prognostic role of clinicopathological variables and the mutational status of BRCA1/2 have also been investigated. Methods: This retrospective, single-institutional study included women with platinum-sensitive lymph node recurrence underwent to SL between June 2008 and June 2018. Univariate and multivariate analysis was performed to evaluate the impact of clinical parameters, and BRCA1/2 mutational status on post salvage lymphadenectomy progression-free survival (PSL-PFS). Results: As of June 2019, the median follow-up after SL was 30 months, and the relapse has been documented in 48 (56.5%) patients. In the whole series, the median PSL-PFS was 21 months, and the 3-year PSL-PFS was 36.7%. The median PSL-PFS, according to patients with ILNR (N = 71) versus patients with lymph-nodes and other sites of disease (N = 14), was 27 months versus 12 months, respectively. Univariate analysis of variables conditioning PSL-PFS showed that platinum-free interval (PFI) ≥12 months, normal Ca125 serum levels, and number of metastatic lymph-nodes ≤3 played a statistically significant favorable role. In multivariate analysis, PFI duration ≥12 months and the number of metastatic lymph nodes ≤3 were shown to keep their favorable, independent prognostic value on PSL-PFS. Conclusions: In the context of SL, the patients with long PFI and low metastatic lymph node numbers at ILNR diagnosis have the best outcome. The BRCA mutational status seems not associated with clinical variables and PSL-PFS, differently from other sites of disease in ROC patients.